An Ordovician lamprophyre dyke at Machias Seal Island, New Brunswick, Canada - McHone, J. Gregory; Barr, Sandra M.; Hames, Willis E. (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2025)
A narrow (<1 m) fine- to medium-grained lamprophyre dyke intruded Neoproterozoic monzodiorite on the eastern side of Machias Seal Island in the northern Gulf of Maine about 19 km southwest of the island of Grand Manan, New Brunswick, Canada. The dyke is near-vertical and trends 015° to 025°, with two shoreline exposures about 680 m apart assumed to be the same dyke. The dyke is notably dark and dense, with a granular broken surface. Thin sections reveal abundant euhedral outlines of olivine pseudomorphs in a groundmass of small (<0.2 mm) grains of brown amphibole (kaersutite) and augite, with ocelli and interstitial patches of albite, calcite, and analcite. The olivine phenocrysts have been completely replaced by chlorite, whereas other ferromagnesian minerals remain unaltered. Accessory minerals include abundant needle-shaped apatite, magnetite, and cubic pyrite. Another small dyke on the western side of the island is less mafic, non-porphyritic, and consists of fine- to medium-grained plagioclase and clinopyroxene, which are highly altered; we interpret it to be unrelated to the lamprophyre dyke to the east. Whole-rock chemistry shows that the lamprophyre dyke is camptonite, similar to some Mesozoic lamprophyre dykes of Maritime Canada and New England, USA, of which the nearest example is about 110 km to the southwest in coastal Maine. Laser fusion 40Ar/39Ar analyses of single kaersutite crystals (n = 12) yield an age distribution with a single, well-defined mode of ca. 468 Ma; incremental heating analyses of small aliquots of crystals show evidence of some radiogenic 40Ar loss and yield a mean plateau age of 478.7 ± 1.9 Ma. This Early Ordovician age and the accompanying uncertainty are interpreted to represent the time of crystallization for the camptonite dyke. The camptonite of Machias Seal Island is older than other Paleozoic and Mesozoic mafic dykes in the region. It is interpreted to be the product of partial melting of a metasomatised mantle during the Penobscot orogeny.